(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This study examines three mitres from the collection of the Metropolitan Cathedral of Belém, which belonged to Archbishop Dom Alberto Gaudêncio Ramos, objects of significant historical and religious relevance to the Catholic Church in the Amazon. The main issue focuses on the conservation status of these pieces, exacerbated by adverse environmental conditions and inadequate conservation practices. In this context, an interdisciplinary analysis is proposed in the fields of History, Theology, and collection conservation, emphasizing the importance of preventive conservation for protecting these textile artifacts, given their current condition. The mitres, symbols of episcopal dignity, are described in terms of their composition and structure, highlighting the vulnerability of the materials used in their production. Conservation requires a detailed diagnosis encompassing the history of the textiles, the materials employed, and storage conditions. The study also underscores the need to document and organize the space where the mitres are stored, proposing immediate preservation actions, such as the use of inert materials and controlled cleaning techniques. With the musealization of the mitres and the establishment of a small museum in the Cathedral of Belém, it is essential to expand safeguarding initiatives to ensure their long-term protection and reaffirm the profound historical, liturgical, and cultural significance of these mitres for the Church and the Catholic culture of the Amazon.